Lung Ultrasound in Early Diagnosis of Neonatal Ventilator Associated Pneumonia before Any Radiographic or Laboratory Changes. (6th November 2016) - Ibrahim, Mohammed; Omran, Ahmed; Ibrahim, Mostafa; Bioumy, Nouran; El-Sharkawy, Sonya
Abstract : Neonatal pneumonia is reported to be the primary cause of neonatal respiratory failure and one of the common causes of neonatal hospitalization and death in developing countries. Chest X-ray was considered the gold standard for diagnosis of neonatal pneumonia. Lung ultrasonography has been described as a valuable noninvasive tool for the diagnosis of many neonatal pulmonary diseases. We report a case of ventilation associated neonatal pneumonia with very early diagnosis using lung ultrasound before any significant radiographic changes in chest X-ray or laboratory findings suggestive of infection.